Pakistan - Federal Procurement Baseline Indicator Systems Assessment - World Bank (World Bank, 2012)
The Baseline Indicators (BLIs) assessment has been conducted by the Development Partners and the Government of Pakistan as a precursor to carrying forward the Government's efforts to upgrade the Country Procurement Systems (CPS) to international standards and to help it assess the level and type of technical assistance required for achieving this objective. The assessment, being the first phase of a comprehensive procurement performance assessment, covered the four pillars as well as all the indicators and sub-indicators in each pillar based on a review of the existing regulatory framework and the institutional and operational arrangements and as provided for in the Organization for Economic Development (OECD) Development Advisory Committee (DAC) guidelines. While the views expressed in the report were the subject of discussions at the stakeholders' workshop, they do not necessarily represent the views of the Government of Pakistan. The result indicates that compared to the standard required for a transparent, efficient and effective procurement system, the existing system in Pakistan needs to be improved substantially. The highest achieved rating is for pillar one, the legislative and regulatory framework, which is an amalgam of specific legislation and sub-legislation impacting the procurement activity of the government and the older legislative instruments affecting the overall operations of the public and/or the private sectors. The Public Procurement Regulatory Authority (PPRA) is the apex body of the institutional framework (pillar two) governing the public procurement arena. The Pakistan Engineering Council (PEC) was involved as a member of the Kazi committee to prepare a standard bidding document and standard General Conditions of Contract (GCC) for all engineering contracts. Improvements in improving the procurement market and operations (pillar three) can only happen when substantial progress has been achieved in reforming pillars one and two of the procurement framework. Integrity and efficiency in the public procurement system (pillar four) is the ultimate goal of all procurement systems and is not easily achieved. This, therefore, requires changes not only within the specific procurement related legislation, but also across a raft of other legislation to ensure an overall enabling environment. Coupled to this is the need to motivate decision makers and civil society to actively participate in ensuring the implementation of the revised legislation. This will require several years, but the effort could be started at an early stage of the reform process.